2021
DOI: 10.4081/aiua.2021.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Minimal invasive percutaneous nephrolithotomy (Mini-PCNL) in children: Ultrasound versus fluoroscopic guidance

Abstract: Background: Miniaturization of endoscopic instruments in percutaneous nephrolithotomy (PCNL) allowed less invasive procedures with low complication rates, especially in children. This study was conducted to evaluate the safety and efficacy of ultrasonography-guided (USG) versus fluoroscopy-guided (FG) mini-PCNL in children.Materials and methods: This is a retrospective comparative study conducted from June 2015 to June 2020. The sample included 70 children (35 pateints underwent USG mini-PCNL and 35 pateints u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 25 publications
(32 reference statements)
0
21
0
Order By: Relevance
“…Warm saline solution was performed as irrigation to avoid hyponatremia and hypothermia. The US confirmed the operation's stone-free status at the end [ 8 , 9 ]. The previous nephrostomy tube was left at the end of the procedure ( Figure 2 ).…”
Section: Patient and Observationmentioning
confidence: 89%
See 2 more Smart Citations
“…Warm saline solution was performed as irrigation to avoid hyponatremia and hypothermia. The US confirmed the operation's stone-free status at the end [ 8 , 9 ]. The previous nephrostomy tube was left at the end of the procedure ( Figure 2 ).…”
Section: Patient and Observationmentioning
confidence: 89%
“…Conventional PCNL procedure for treating stones in the transplanted kidneys has been a well-accepted therapeutic intervention explained by numerous surgeons over the last decade [ 1 , 6 , 8 ]. However, information regarding mini-PCNL for transplanted kidneys is limited, with few reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a systematic review revealed no significant difference between ultrasonography and fluoroscopy regarding bleeding [ 15 ], we prefer ultrasonography-guided PNL, because the advantages of using the ultrasonography for guidance include decreased exposure to radiation and lower overall cost, decreased operation time and detection of radiolucent stones [ 16 , 17 ]. Moreover, it is useful for decreasing the rate of visceral injury due to better visualization of the surrounding viscera and the depth of needle penetration, and for avoiding vascular injury by adding Doppler flow imaging [ 18 ]. In the present study, we conducted ultrasonography-guided PNL for all the patients.…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, Baydilli et al ( 11 ) reported their single-institution experience in 206 pediatric patients undergoing mini-PCNL for kidney stones with a success rate of 80.6% after the first session, increasing to 87.9% after auxiliary treatments. In a following study comparing the efficacy and the safety of ultrasonography-guided vs. fluoroscopy-guided “mini-PCNL” in children, Eslahi et al ( 12 ) reported higher stone-free rates: 97.1% in the ultrasonography-guided group ( n = 35 patients) and 94.3% in the fluoroscopy-guided group ( n = 35 patients). Similar results were published more recently: Mahmood ( 13 ) in 143 patients experienced a 92.4% of stone-free rate after a single “mini-PCNL” session independently by patient's age.…”
Section: Miniaturized Technologiesmentioning
confidence: 99%